An empirical study of firm productivity growth based on the dynamic selection model: Effects on the recent decline in Korean exports. (1st October 2021) - Son, Nyeong Seon; Hur, Jung
Abstract: Export and productivity growth in the Korean manufacturing sector have both been slow since 2011. To understand this relationship, we examine the productivity distributions of manufacturing firms in Korea by applying the dynamic selection model developed by Sampson (2016). The fitness of the dynamic selection model suggests that a slowdown in the market selection mechanism may be a crucial contributor to the stagnant growth in the productivity. In addition, we find that the productivity difference between exporting firms and non‐exporting firms has decreased and the low productivity growth of firms exporting to non‐foreign affiliates has contributed to this trend.